Teaching Competencies for Educational Inclusion in Telesecundaria, Zone 13, Tabasco - García Ruiz, Alejandro (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
This study aims to analyze the teaching competencies required for educational inclusion in Telesecundaria School Zone 13 in Tabasco, in order to propose training strategies that strengthen the teaching-learning process for students in vulnerable situations.The research follows a quantitative, exploratory-descriptive approach with a non-experimental design, using a survey applied to six teachers from the “Guillermo Prieto” telesecundaria school. The theoretical framework is based on Piaget’s constructivism, Vygotsky’s sociocultural theory, and Gardner’s theory of multiple intelligences, which support diversity-oriented educational practices.The results show that, although teachers demonstrate conceptual knowledge and a positive disposition toward inclusion, there are areas for improvement in the use of diversified teaching strategies, information and communication technologies, and knowledge of current educational policies. Additionally, key competencies such as the development of differentiation strategies are lacking.The main limitation of the study is the small sample size, which prevents generalization but allows for a contextualized diagnostic of the studied setting. This research provides value by offering context-based knowledge and practical teacher training proposals aligned with current educational policies.It is concluded that strengthening continuous teacher training is essential for developing inclusive competencies, promoting equitable learning environments and effective attention to student diversity.
Keywords: Teaching competencies; Inclusive education; Teacher training; Teaching strategies; Secondary education; Diversity in education